Comparative study on anti traficking in person act 2007,anti money laundering act 2001 with racketeer influeced corrupted organization (RICO) act (1970) / Muhammad Amin Shamsudin...[et al.] - Shamsudin, Muhammad Amin; Mohd Tahir, Nabila Husna; Hafiz, Nur Sakinah; Yasmi, Nurul Aqilah Hani (Faculty of Law, 2013)
The research looks on a comparative study between the legislation in Malaysia and United States in dealing with organized crime. The definition of organized crime as discussed in Chapter 1 specifies that the tenn organized crime derived its meaning frOin criminal networks that forge bonds across borders. Chapter 2 would be focused on the study of the law in United States in dealing with oganised crime which is the RICO Act. The Act was passed to control the infiltration of organized crime within corporate businesses and to prosecute the business practices of criminal cartels. Meanwhile, the law in Malaysia in dealing with organized crime would be focused on the Anti-Money Laundering Act 2001 and the Anti Human Trafficking In Person Act 2007. The Anti-Money Laundering Act 2001 as discussed in Chapter 3 purported in prohibiting a money launderer from enjoying from his illegal proceeds for either a short tenn or long period of time. On the other hand, the Anti Trafficking In Human 2007 under Chapter 4 intended to eliminate human trafficking involving Malaysian citizens or non-eitizens using a holistic approach. Apart from looking at the objective of those Acts, this research would also cover the legal provisions on which several distinctions can be drawn. Thus, our study on the comparative study between Malaysia and the United States as provided in Chapter 5 will be focusing on the elements of the offence or predicate offence, the objective and mechanism of the Acts, the conduct of the prosecution and the effectiveness of the enforcement agency. This research would be conducted in a qualitative method with library-based materials, online searching and also interactive interviewing. Hence, our study would be limited to comparison between RICO Act and the AntiMoney Laundering Act 2001 and the Anti-Trafficking in Human 2007 and at the end of Chapter 6 we would provide recommendations in dealing with organized crime, particularly in Malaysian legislation, for both short tenn and long tenn.